P45 Perception of ability differs in individuals with chronic ankle instability depending on condition severity. (17th September 2017) - Smith, MD; KY, Ng; Rankin, J; Mazzei, J; Williams, T; Bancroft, S; Tucker, K
Abstract : Study Design: Cross-sectional study. Objectives: To determine if estimation of performance of a maximal single-leg-hop (SLH) differs between individuals with and without chronic ankle instability (CAI), and those of differing CAI severity. A secondary aim was to determine if ankle tape alters estimated and actual performance. Background: The capacity to estimate physical ability is effected by pain. It is possible that factors characteristic of CAI, such as ankle instability and giving way, may also influence accuracy of performance estimation. Taping is commonly used to prevent recurrent injury and manage symptoms in CAI. As ankle tape is associated with improved self-report ankle stability, it may also influence perceived and/or actual physical performance. Methods and Measures: Twenty-two individuals with CAI (10 less and 12 more severe; based on Cumberland Ankle Instability Tool (CAIT) score of <24) and 12 controls participated in this study. Participants estimated their SLH distance and then performed three maximal SLH's, both with and without ankle taping. Data was normalised to height. Perceived ankle stability, ankle confidence and task confidence were also recorded. Results: Irrespective of tape, CAI participants hopped further than controls (p=0.03), and estimated they would hop further than controls (trend; p=0.05). Participants with less severe CAI estimated they would hop further, hopped further, and had a higher expected/actual performance ratio (i.e. they better estimated performance ability) than controls and more severe CAI (all p<0.03). The application of tape did not affect distance measures in any group (all p>0.06). All groups reported greater ankle stability with than without tape (p=0.002). Conclusion: An improved ability to accurately estimate performance in individuals with less severe CAI may relate to physical attributes of the group, or be part of a strategy to deal with CAI symptoms. Despite increased perceived stability, ankle tape does not affect perceived or actual hopping performance.